Commercially toothbrush bristle protectors contamination and agents used for disinfection. In vitro study (Research, Society and Development, 2025)
This study aimed to characterize the contamination of commercially Purchased Toothbrush Bristle Protectors (PCED) and the effectiveness of different chemical and physical disinfection agents. A sterile swab was passed over both sides of the inside of 14 PCED, which were placed in test tubes with sterile nutrient broth and incubated at 37°C for 48 hours. Petri dishes were seeded in triplicate, and contamination was characterized by scoring the number of colony-forming units present. PCED were divided into groups (G) for 1 minute and scrubbed with a sterile swab containing: G1 – saline solution; G2 – 0.12% chlorhexidine digluconate without alcohol; and G3 – application of UV-C radiation. The same microbiological methodology was applied to characterize CBCP disinfection. Statistical tests ANOVA assisted by the t-test and t-test were applied to analyze the related samples, both with a significance level of 5%. Contamination was observed in 35.7% of the PCED. G2 and G3 proved effective in reducing PCED contamination (p